2023
DOI: 10.1111/cns.14079
|View full text |Cite
|
Sign up to set email alerts
|

Human‐induced pluripotent stem cell‐derived cerebral organoid of leukoencephalopathy with vanishing white matter

Abstract: Introduction:Leukoencephalopathy with vanishing white matter (VWM) is a rare autosomal recessive leukoencephalopathy resulting from mutations in EIF2B1-5, which encode subunits of eukaryotic translation initiation factor 2B (eIF2B). Studies have found that eIF2B mutation has a certain influence on embryonic brain development.So far, the effect of the eIF2B mutations on the dynamic process of brain development is not fully understood yet.Aims: Three-dimensional brain organoid technology has promoted the study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…This finding can explain the presence of microcephaly in patients with the congenital form of VWM. The results of this study suggest that mutations in eIF2B genes cause a delay in the development of neural stem cells of the brain organoids, which in turn affects subsequent glial cell development [66].…”
Section: Leukoencephalopathy With Vanishing White Matter (Vwm)mentioning
confidence: 82%
See 1 more Smart Citation
“…This finding can explain the presence of microcephaly in patients with the congenital form of VWM. The results of this study suggest that mutations in eIF2B genes cause a delay in the development of neural stem cells of the brain organoids, which in turn affects subsequent glial cell development [66].…”
Section: Leukoencephalopathy With Vanishing White Matter (Vwm)mentioning
confidence: 82%
“…Alterations in this factor influence embryonic brain development, as demonstrated by the neuropathological characteristics of two fetuses carrying EIF2B5 gene mutations [109]. To investigate the pathophysiological mechanisms in the dynamic process of VWM development, wild-type and eIF2B mutant brain organoids were developed from iPSCs [66]. The mutant organoids showed a smaller size in the early stages, with increased apoptosis due to the overactivation of the unfolded protein response.…”
Section: Leukoencephalopathy With Vanishing White Matter (Vwm)mentioning
confidence: 99%
“…In fact, coculture models of VWMD astrocytes and control oligodendrocyte progenitor cells (OPCs) have shown stalled oligodendroglia maturation into myelin-forming cells potentially linked to exaggerated secretion of glucosaminoglycan hyaluronan, a major component of the brain ECM profile, later confirmed in post-mortem VWMD tissues (Bugiani et al, 2013;Dooves et al, 2016). A recent secretomics profiling of VWMD astrocytes demonstrates impairment of classic OPC maturation markers (Deng et al, 2023). Others have shown that stem cell-derived and iPSCderived neurons and oligodendrocytes from VWMD patients grown normally in culture while astrocytes exhibit classic VWMD impairments (Dietrich et al, 2005;Zhou et al, 2019).…”
Section: Clinical Diagnosis and Neuropathology Of Vwmdmentioning
confidence: 99%
“…Park et al elegantly presented a microfluidic platform using tricultures of AD neurons, astrocytes, and microglia that mimicked microglial spatial recruitment and neuroinflammation markers that could not be observed in monocultures of the same cells (Park et al, 2018). Interestingly, a 3D organoid with VWMD patient-derived iPSCs has been recently developed and fully recapitulated VWMD's main pathological hallmarks (GFAPδ expression, immature oligodendrocytes, sparse myelin) (Deng et al, 2023), while cultured astrocytes from VWMD mutant eIF2Bε R191H mice lose in vivo diseased phenotype (hypersensitive ISR) and instead behave like healthy astrocytes (Wisse et al, 2018); altogether showing that future studies should devise and include cocultured platforms to investigate VWMD pathomechanisms.…”
Section: Limitations and Commentary Of Future Researchmentioning
confidence: 99%